Breaking laws : violence and civil disobedience in protest - Sommier, Isabelle; Hayes, Graeme, 1967-; Ollitrault, Sylvie (Protest and social movements., 2019)
This book questions the complex relationship between social movements and violence through two contrasted lenses, first through the short-lived radical left wing post '69 revolutionary violence and secondly in the present diffusion of civil disobedience actions, often at the border between non-violence and violence. This book shows how and why violence occurs or does not, and what different meanings it can take. The short-lived extreme left revolutionary groups that grew out of May '68 and the opposition to the Vietnam War (such as the German Red Army Faction, the Italian Red Brigades, and the Japanese Red Army) are without any doubt on the violent side. More ambiguous are the burgeoning contemporary forms of "civil" disobedience, breaking the law with the aim of changing it. In theory, these efforts are associated with nonviolence and self-restraint. In practice, the line is more difficult to trace, as much depends on how political players define and frame political violence and political legitimacy